2006
DOI: 10.1097/01.aog.0000195968.80447.fa
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Hormone in Singleton and Twin Pregnancy: Importance of Gestational Age–Specific Reference Ranges

Abstract: Coassolo and colleagues are to be congratulated for building a very large database on women with prior cesarean. 1 This important work and its related findings should help in the difficult task of counseling a patient between a trial of labor and elective repeat cesarean. In their latest publication, 1 they concluded that the risk of uterine rupture was not increased at or beyond 41 weeks of gestation. The rate of uterine rupture in 1,643 women who delivered at or beyond 41 weeks (1.46%) was almost significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
2
6

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(73 citation statements)
references
References 3 publications
4
61
2
6
Order By: Relevance
“…w e demonstrate elevated T4 she is really in state o f concluded that the induced elevation of T4 may b e hyperthyroidism but, it is the new physiological condition responsible for the morning sickness, nausea and and the metabolic regulation of pregnant women which vomiting of first-trimester of pregnancy, this finding is in realized and on that base, extra thyroxin requirement is agreement with many other studies in different part of requested, T4 is elevated, not for the sake o f the world (Al-Yatama et al, 2002;Caffrey, 2000; hyperthyroidism, but for the sake growing fetus demand Haddow et al, 2008;Sheehan, 2007). and the maternal new physiological conditions, therefore Laboratory assessment of thyroid function test the establishment of reference intervals and the during early stage of pregnancy and measurement of TSH, methodology of thyroid hormone measurements in each T4,T3,TBG, hCG and thyroid auto-antibodies, all help the region is a great importance (Dash et al, 2005). We argue clinician to properly address a pregnant women with that if the maternal serum thyroxin level, is at normal level hyperthyroidism.…”
Section: During Pregnancymentioning
confidence: 98%
“…w e demonstrate elevated T4 she is really in state o f concluded that the induced elevation of T4 may b e hyperthyroidism but, it is the new physiological condition responsible for the morning sickness, nausea and and the metabolic regulation of pregnant women which vomiting of first-trimester of pregnancy, this finding is in realized and on that base, extra thyroxin requirement is agreement with many other studies in different part of requested, T4 is elevated, not for the sake o f the world (Al-Yatama et al, 2002;Caffrey, 2000; hyperthyroidism, but for the sake growing fetus demand Haddow et al, 2008;Sheehan, 2007). and the maternal new physiological conditions, therefore Laboratory assessment of thyroid function test the establishment of reference intervals and the during early stage of pregnancy and measurement of TSH, methodology of thyroid hormone measurements in each T4,T3,TBG, hCG and thyroid auto-antibodies, all help the region is a great importance (Dash et al, 2005). We argue clinician to properly address a pregnant women with that if the maternal serum thyroxin level, is at normal level hyperthyroidism.…”
Section: During Pregnancymentioning
confidence: 98%
“…47,49 Of note, it has been reported that the upper 95% Cl for plasma TSH in the first trimester is 2.5 mU=L. 47 It is known that the TSH level descends 60%-80% by week 10 and recovers slowly thereafter, but it may not reach the preconception normal range until gestation ends. 45 …”
Section: Diagnosis Of Suspected Diseasementioning
confidence: 99%
“…Interpretation of thyroid function tests should be trimester-specific, 28,47,48 and locally generated trimester-specific reference levels should be applied when available. 47,49 Of note, it has been reported that the upper 95% Cl for plasma TSH in the first trimester is 2.5 mU=L. 47 It is known that the TSH level descends 60%-80% by week 10 and recovers slowly thereafter, but it may not reach the preconception normal range until gestation ends.…”
Section: Diagnosis Of Suspected Diseasementioning
confidence: 99%
“…Pregnant women of Moroccan, Turkish or Surinamese descent residing in the Netherlands have TSH values 0.2-0.3 mIU/l lower than Dutch non pregnant women [87]. TSH concentrations are lower in multiple pregnancies since hCG concentrations are higher [88].…”
Section: Diagnosismentioning
confidence: 95%